1978
DOI: 10.1126/science.151328
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Adipocyte Number as the Basis for Perirenal Depot Growth in Adult Rats

Abstract: The mass of the perirenal adipose depot in male Fischer 344 rats increases between 6 and 18 months of age. This increase is due to an increase in the number of adipocytes in this depot, in contrast with the concept that adipocyte number is constant throughout adult life. The epididymal depot increases in mass between 6 and 18 months of age by adipocyte hypertrophy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 11 publications
2
42
0
1
Order By: Relevance
“…Whether changes in the release of this or other neuromodulators could be relevant for the lipolytic resistance in obesity remains to be elucidated. Obesity is characterized by an increase in number and size of fat cells (39,40). One could imagine that a disproportional increase in fat cell mass in relation to efferent sympathetic nerve fibers and/or blood vessels may serve as an explanation for the present results.…”
Section: Discussionmentioning
confidence: 59%
“…Whether changes in the release of this or other neuromodulators could be relevant for the lipolytic resistance in obesity remains to be elucidated. Obesity is characterized by an increase in number and size of fat cells (39,40). One could imagine that a disproportional increase in fat cell mass in relation to efferent sympathetic nerve fibers and/or blood vessels may serve as an explanation for the present results.…”
Section: Discussionmentioning
confidence: 59%
“…These authors also suggested that after a specific mean size is achieved for existing fat cells, unknown events trigger the formation of new fat cells. Bertrand and Masoro (1978) also reported an increase in adipocyte number in the perirenal fat pad without dietary manipulations when Fisher rats were experimentally controlled from 6 to 18 months of age, but failed to observe the same effect on the epididymal fat pad.…”
Section: Nutritional Influencesmentioning
confidence: 99%
“…Variations in cellularity due to differences among species , among fat depots within species (Moody and Cassens, 1958;Anderson et al, 1972;Hood and Allen, 1973b;Bertrand and Masoro, 1978) and even within the same fat depot contribute to a lack of understanding on adipose tissue development. Waters (1909) stated that the amount of adipose tissue in an animal is primarily dependent upon the number and size of the fat cells.…”
Section: Adipose Tissue Traitsmentioning
confidence: 99%
See 2 more Smart Citations